DISABLED ANALYSIS OF CERAMIC PRODUCTS ON THE GLASS PROCESS USING THE SEVEN TOOLS METHOD (CASE STUDY: PT. NJMX SURABAYA - Yunia Dwie Nurcahyanie; Titik Koesdijati (UNIPA PRESS, 2020)
In the production process of quality is very off at PT. NJMX, a company engaged in the manufacture of ceramics where the quality of a good ceramic surface does not have any disability is expected by consumers. This study aims To identify the disability of ceramic products by using the seven tools method on the glaze process, applying the seven tools method as an effective tool to improve productivity and product quality in the process of making ceramic diunit glaze. From the data processing, it can be known that the type of defect that has a high percentage obtained is the pinhole with the total average defect is 57 units, other causes are Dimpel 53 units, 50 glaze cracking, 48 lines and 45 units waves. Of the five types of defects the highest percentage is pinhole defect with a total percentage of 22.60%, while for dimpel 20.90%, cracked glaze 19.66%, 18.93 and 18.93% waves. And obtained the average value of sigma 3.58 with DPMO value of 13.553%.